SISTEM INFORMASI PERSEDIAAN PUPUK PADA PT. GRESIK CIPTA SEJAHTERA - Mochamad Yusuf Romdoni; Rizki Fatullah; Irma Yunita Ruhiawati (LPPM Unbaja, 2020)
The purpose of this study was to analyze the fertilizer supply system at PT.Gresik Cipta Sejahtera which is a system that helps process fertilizer inventory data so that it is expected to provide input on how to implement better data processing in the current era of information technology, this fertilizer supply system is carried out. with several stages of coordination through incoming letters of request to data collection based on recaptulation from the inventory by utilizing semi-computerized parts related, seeing that there are scattered data resulting in frequent inconsistencies of data so that data errors encourage checking that repeated so that a lot of time and energy is wasted, this is deemed ineffective and efficient. With the existence of computerization, it can make it easier for companies to monitor the warehouse section so that work in the warehouse section is more efficient and efficient, so that it can reduce obstacles that have occurred so far. The analysis method used to describe the inventory system at PT. Gresik Cipta Sejahtera uses the method of observation, interviews, and uses literature. The tools used to describe the system using DFD (Data Flow Diagram)